George Crumb - between reflection upon nature and contemplating it - Szoka, Marta (Interdisciplinary Studies in Musicology, 2018)
The author investigates the unique aesthetic program of George Crumb, one of the most important contemporary American composers. Crumb certainly occupies a unique place in the music of 20th century, not only because of his cultural background, or originality of artistic expression, but first of all, due to the presence of most dilemmas of the contemporary culture in his music. The question about the form of a relationship between human beings and nature at the turn of 20th/2ist century is one of them. In his artistic output Crumb remains an advocate of a concept of music which, as the most spiritual and magical of all arts, derives from deep reserves of human psyche on the one hand and from primal forces of nature, on the other one. The analytical aspects of the paper concern the problems of onomatopoeic imitation of the sounds of birds and a whale, symbolic allusions to the other composers (Debussy, Mahler), the concept of “larger rhythms of nature”, the phenomenon of echo and its forms in Crumb’s music, his search of natural pre-sounds of music (resulting in using non-traditional instruments), the idea of distant music, etc. Especially three pieces: An Idyll of the Misbegotten, Vox balaenae and Echoes of Time and the River are considered as the most characteristic.